Intake and digestibility for sheep and goats consuming supplementary Acacia brevispica and Sesbania sesban - Woodward, A.; Reed, J.D. (Elsevier, 1995)
The effect two East African browses, A. brevispica and S. sesban, on feed digestibility and palatability were described. The browses were fed at three levels of each in combination with vetch (Vicia dasycarpa) and teff straw (Eragrostis abyssinica) in a Latin Square design to sheep and goats. Teff straw had low nitrogen (N) content (0.6 percent), high fiber (neutral-detergent fiber (NDF) = 72 percent), but low lignin (5.3 percent) and high true digestibility (73 percent). A. brevispica and vetch had similar amounts of NDF (43 and 37 percent) but A. brevispica had twice as much lignin, therefore lower true digestibility. A. brevispica also contained proanthocyanidins, which were absent in other feeds. S. sesban had low fiber (NDF = 21 percent), low lignin (3 percent) and high true digestibility (90 percent). Sheep had lower refusals of browse and higher intake rates than goats. Sheep refused only diets containing A. brevispica, perhaps because of its proanthocyanidin content. Both A. brevispica and vetch hay had reduced palatability for goats, making it impossible to separate the effect of tannins from that of fiber. although it has been suggested that tannins reduce the digestibility of feed by inhibiting rumen microbes, there seemed to be no such effect in this case because the microbial and endogenous fraction of feces (MI), was constant across diets. There was less fecal metabolic N in diets containing S. sesban, as measured by the N concentration of netural-detergent solubles of feces, which may be best explained by the higher fiber content of A. brevispica and vetch rather than by tannins.